SAT0380 Do Patients Know Best? Reliability of Electronic Patient Self-Evaluation of Swollen and Tender Joints in Psoriatic Arthritis: A Comparison Study with B-Mode Ultrasonography, Physician and Nurse Assessments. (10th June 2014) - Szentpetery, A.; Haroon, M.; O'Flynn, E.; Gallagher, P.; Alraqi, S.; FitzGerald, O.
Abstract : Background: 68 tender (TJC) and 66 swollen joint counts (SJC) are recommended for disease activity assessment in psoriatic arthritis (PsA). However there are time constraints and these counts may not be performed. It has been shown in rheumatoid arthritis that patient's self-reported joint counts correlate well with functional disability, pain and global disease severity. Information concerning patients' self-assessed joint counts however is limited in PsA. Objectives: The aim of this study is to evaluate the reliability of patient self-assessed joint counts versus joint counts obtained by a physician, a nurse and B-mode ultrasonography (US) in PsA. Methods: PsA patients fulfilling the CASPAR criteria were recruited. Following a training session on the detection of tender and swollen joints by a nurse, each patient assessed their 68 joints using an electronic digital mannequin on touchscreen. A joint examination by a different nurse and a rheumatologist, both blinded to the patients' clinical data was completed. US evaluation was performed by a further consultant rheumatologist on 34 joints assessing wrists, MCPs and PIPs, ankles and MTPs, and all extensor/flexor tendons of the fingers and toes. Presence of joint effusion, synovial proliferation and tenosynovitis on grayscale (GS); and synovitis/tenosynovitis on power Doppler (PD) signal were evaluated. Results: 43 patients (29 female and 14 male) were enrolled to the study with a mean age of 51 (±13.5) years. Focusing on the 34 joints also assessed by US, mean TJC assessed by the patients, physician and nurse was 9 (±8.3), 7 (±7.4) and 7 (±6.9), mean SJC was 4 (±5.6), 1 (±1.8) and 3 (±3.2) respectively. Mean number of affected (swollen or tender) joints as per patient, physician, nurse and US evaluation was 10 (±8.2), 7 (±7.1), 8 (±7) and 6 (±4.4), respectively. Patient and nurse-assessed SJC was significantly higher than physician-counts (p=0.0007; p=0.013, respectively). The number of affected joints was higher as evaluated by patients compared to physicians and US (p=0.019; p=0.012, respectively). Joint effusion was detected by US in 72%, synovitis in 79% on GS and 70% on PD and 30% of the patients had tenosynovitis. TJC and the number of affected joints did not correlate significantly with any of the US measurements irrespective of the assessors. Patients SJC significantly correlated with US-assessed joint effusion, and with synovitis (GS and PD). Physician and nurse-reported SJC correlated with US-derived synovitis scores only. Conclusions: Patients scored their SJC and number of affected joints higher than physicians and US measurements. Patient-reported SJC correlated with both effusion and synovitis as detected by US suggesting that patients' self-evaluated SJC may be valid in routine clinical practice for monitoring disease activity in PsA. Disclosure of Interest: A. Szentpetery: None declared, M. Haroon: None declared, E. O'Flynn: None declared, P. Gallagher: None declared, S. Alraqi: None declared, O. FitzGerald Grant/research support: Pfizer, Abbott, BMS, MSD, Roche, UCB, Consultant for: Pfizer, Abbott, BMS, MSD, Janssen, Roche, Speakers bureau: Pfizer, Abbott, Janssen, Roche, UCB DOI: 10.1136/annrheumdis-2014-eular.5435